The Research Landscape of Ferroptosis in Cancer: A Bibliometric Analysis - Li, Guoli; Liang, Yumei; Yang, Hongyu; Zhang, Weiru; Xie, Tingting (Frontiers in Cell and Developmental Biology, 2022)
Background: Ferroptosis is a novel programmed cell death coined in 2012, which has been found playing important roles in human health and disease. In the past decade, ferroptosis research has been seen booming growth worldwide. The aim of this study was to visualize the scientific outputs and research trends of ferroptosis in the field of cancer. Methods: The raw data of publications were retrieved from the Web of Science Core Collection on December 19, 2021. The information of impact factor (IF) and Journal Citation Reports (JCR) division were obtained from the website of Web of Science. Two kinds of software (CiteSpace and VOSviewer) were used to perform visualized analysis. Results: From 2012 to 2021, total 1833 publications related to ferroptosis in cancer were identified for final analysis. The annual number of citations and publications grew exponentially over the past decade. China (1092) and USA (489) had the highest number of publications; Central South University and Guangzhou Med University were the most productive institutions. Daolin Tang and Scott J Dixon were the most active authors ranked by most productive and co-cited, respectively. The journals with the highest output and co-citation frequency were Biochemical and Biophysical Research Communications and Cell, respectively. Among the 1833 publications, four were identified with citations more than 1000 times. Six co-cited references had a citation burst duration until 2021. Analysis of keywords suggested the current research of ferroptosis in cancer clusters in 9 hotspots and newly emerging frontier may be “multidrug resistance”. Conclusion: Cancer research is the major area of active research in ferroptosis. Our results provide a global landscape of the ferroptosis research in cancer from 2012 to 2021, which serve as a reference for future studies in this field.